2005
DOI: 10.1099/vir.0.81260-0
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus intracellular enveloped virions move to the cell periphery on microtubules in the absence of the A36R protein

Abstract: Vaccinia virus (VACV) intracellular enveloped virus (IEV) particles are transported to the cell periphery on microtubules where they fuse with the plasma membrane to form cell-associated enveloped virus (CEV). Two IEV-specific proteins, F12L and A36R, are implicated in mediating transport of IEV. Without F12L, virus morphogenesis halts after formation of IEV, and CEV is not formed, whereas without A36R, IEV was reported not to be transported, yet CEV was formed, To address the roles of A36R and F12L in IEV tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 29 publications
5
69
0
Order By: Relevance
“…Suggesting that MDAs may have virus-specific effects, we and others have observed that, while they enhance rhabdoviruses, microtubule destabilizers robustly inhibit vaccinia growth 36 . However, other viruses have been reported to grow at least equivalently in cells with destabilized microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting that MDAs may have virus-specific effects, we and others have observed that, while they enhance rhabdoviruses, microtubule destabilizers robustly inhibit vaccinia growth 36 . However, other viruses have been reported to grow at least equivalently in cells with destabilized microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…For vaccinia virus and African swine fever virus (DNA viruses), both microtubule-dependent transport and actin-based motility are used to drive viral particles (36)(37)(38). Intracellular vaccinia virus particles are transported along microtubules with speeds of 500-750 nm/s (35,39). The actin-based propelling of extracellular vaccinia virus particles takes place with velocities of ∼170 nm/s (36).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular enveloped Vaccinia virus particles move from their perinuclear assembly site to the plasma membrane along microtubules [58][59][60][61][62][63] . These particles fuse with the plasma membrane, but remain attached as cell-associated enveloped virus (CEV) 64 .…”
Section: Viral Assembly and Egressmentioning
confidence: 99%